2018
DOI: 10.1029/2018ea000447
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Assimilating the FORMOSAT‐3/COSMIC and FORMOSAT‐7/COSMIC‐2 RO Data on the Midlatitude and Low‐Latitude Ionospheric Specification

Abstract: Global Navigation Satellite System (GNSS) Radio Occultation (RO) missions, such as the Formosa Satellite‐3/Constellation Observing System for Meteorology, Ionosphere, and Climate (FORMOSAT‐3/COSMIC) and the upcoming FORMOSAT‐7/COSMIC‐2, provide valuable profiling of the ionized atmosphere for the monitoring of space weather. This study shows that the FORMOSAT‐3/COSMIC and FORMOSAT‐7/COSMIC‐2 missions' ability to monitor highly variable ionospheric weather can be considerably extended with the help of data assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The DOI analysis presented here can also be combined with an Observing System Simulation Experiment (OSSE), an approach already used in ionospheric and solar dynamo studies (Hsu et al, 2018;Dikpati, 2017) to help provide a cost-effective approach to the evaluation of the potential impact of new observations. OSSE requires that DA is already implemented and uses independently simulated "data" that are ingested into a different model or a different instance of the same model.…”
Section: Discussionmentioning
confidence: 99%
“…The DOI analysis presented here can also be combined with an Observing System Simulation Experiment (OSSE), an approach already used in ionospheric and solar dynamo studies (Hsu et al, 2018;Dikpati, 2017) to help provide a cost-effective approach to the evaluation of the potential impact of new observations. OSSE requires that DA is already implemented and uses independently simulated "data" that are ingested into a different model or a different instance of the same model.…”
Section: Discussionmentioning
confidence: 99%
“…They focused on assimilating over a period of 24 h under solar minimum conditions. Hsu, Matsuo, and Liu (2018) and Hsu, Matsuo, Yue, et al. (2018) presented observing system simulation experiments (OSSEs) of assimilation of synthetic data that represent both COSMIC and the follow‐on mission COSMIC‐2.…”
Section: Introductionmentioning
confidence: 99%
“…This often hinders the investigation of day‐to‐day ionosphere variations, making it necessary to combine several days of measurements to generate a global density map. On the other hand, numerous studies have demonstrated the capability to reconstruct global ionosphere density through data assimilation techniques (Araujo‐Pradere et al, 2007; Bust et al, 2004, 2007; Chen, Lin, Matsuo, Chen, Lee, et al, 2016; Chen, Lin, Matsuo, & Chen, 2016; Chen et al, 2017, 2019; Fuller‐Rowell et al, 2006; Hajj et al, 2004; Hsu et al, 2014; Hsu, Matsuo, Yue, et al, 2018; Hsu, Matsuo & Liu, 2018; Komjathy et al, 2010; Lee et al, 2012, 2013; Matsuo & Araujo‐Pradere, 2011; Scherliess et al, 2006; Schunk et al, 2005; Sun et al, 2015; Wang et al, 2004; Yue et al, 2014). Recently, Lin et al (2015, 2017) developed the global ionospheric specification (GIS) data assimilation system that can provide global ionospheric electron density on an hourly basis.…”
Section: Introductionmentioning
confidence: 99%